Localised Responses in Urban Areas for Forcibly Displaced Populations: A Case Study of Amman, Jordan in Shelter and Settlements Sector - Patra, Kshirabdhi Tanaya; Krishnan, Sneha (Calibrating Urban Livability in the Global South, 2024)
With the increasing population of internally displaced people, the problem of forcibly displaced population has significantly affected the humanitarian well-being of the population. Jordan hosts around 659500 Syrians, who are among the top refugee populations. Over half of all 26 million refugees and every one in two internally displaced persons were estimated to live in urban areas (UNHCR, 2020). Large populations create socioeconomic disparities. Proximity to essential needs, better economic opportunities, similar cultural practices, and the probability of being granted asylum are key factors for refugees to choose urban areas for their settlement. In this case study, we focus on the city of Amman, Jordan, which has witnessed a much higher number of forcibly displaced populations in recent years among others, and show how localization has been part and parcel of the humanitarian response, especially in the sector of shelter and settlements. We also study the barriers and challenges experienced by the actors and stakeholders in the process.